Quantifying the Impact of Climate Change on Marine Diazotrophy: Insights From Earth System Models - Wrightson, Lewis; Tagliabue, Alessandro (Frontiers in Marine Science, 2020)
Nitrogen fixation is a major source of new nitrogen to the ocean, supporting biological productivity in the large nitrogen-limited tropical oceans. In Earth System Models, the response of nitrogen fixation to climate change acts in concert with projected changes to physical nitrogen supply to regulate the response of primary productivity in nitrogen-limited regions. We examine the response of diazotrophy from nine Earth System Models and find large variability in the magnitude and spatial pattern of nitrogen fixation in both contemporary periods and future projections. Although Earth System Models tend to agree that nitrogen fixation will decrease over the next century, strong regional variations exist, especially in the tropical Pacific which may counteract the response of the Atlantic and Indian oceans. As the climate driven trend of nitrogen fixation emerges by mid-century in the RCP8.5 scenario, on regional scales it may modulate the broad climate trends in productivity that emerge later in the century. The generally poor skill and lack of agreement amongst Earth System Models indicates that the climate response of nitrogen fixation is a key uncertainty in projections of future ocean primary production in the tropical oceans. Overall, we find that the future evolution of nitrogen fixation plays an important role in shaping future trends in net primary production in the tropics, but the poor skill of models highlights significant uncertainty, especially considering the role of multiple concurrent drivers.